Mr. Wizard's experiments for young scientists - Herbert, Don.; Noonan, Daniel (New York : Doubleday, 1990)
Describes the step-by-step procedures and necessary equipment for thirteen science projects and experiments that can be done at home.
6.2
3-6.
3-6
Keywords: Science projects -- Juvenile literature; Science -- Experiments -- Juvenile literature; Experiments; Science projects; Science -- Experiments; Science -- Experiments